16(x+9)=4(36+4x)

Simple and best practice solution for 16(x+9)=4(36+4x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 16(x+9)=4(36+4x) equation:


Simplifying
16(x + 9) = 4(36 + 4x)

Reorder the terms:
16(9 + x) = 4(36 + 4x)
(9 * 16 + x * 16) = 4(36 + 4x)
(144 + 16x) = 4(36 + 4x)
144 + 16x = (36 * 4 + 4x * 4)
144 + 16x = (144 + 16x)

Add '-144' to each side of the equation.
144 + -144 + 16x = 144 + -144 + 16x

Combine like terms: 144 + -144 = 0
0 + 16x = 144 + -144 + 16x
16x = 144 + -144 + 16x

Combine like terms: 144 + -144 = 0
16x = 0 + 16x
16x = 16x

Add '-16x' to each side of the equation.
16x + -16x = 16x + -16x

Combine like terms: 16x + -16x = 0
0 = 16x + -16x

Combine like terms: 16x + -16x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 12k-10-k=3(2k+20) | | 3x^2-36x+109=0 | | 2u^2+6u+13=u^2+10u+25 | | 7m=6m-6 | | 2.1=4.3-1.1w | | 3(2+y)+3=12 | | 4x+2=4(x-6) | | x+13=4x-42 | | y=(50)x+b | | c/2-3.2=26.8 | | -2z=-z+9 | | -5(x-2)+8x=5x-6 | | 36+7n=6(n+7) | | 13=7+21t-16t^2 | | 10-4j-7=-9-7j | | 2x+6=3+6x-7 | | -7625+185t=0 | | 2q=18.92+6.3q | | 13.9j-9.71-8.7=9.43+16.3j | | -4y=-3y-10 | | 7x+4(x-5)=3(x+2)-5 | | 8x-3y=14fory | | 2x+5+6x-1=90 | | 3+10q=6+9q | | 3/4z=-5+1/2 | | 19.03+11.2y=5.1y-17.59-9.13 | | 4(-6x+1)=20-8x | | 335=5x^3 | | 8x+5-2x=-(5x-x) | | 3/4z=-5.5 | | 14.7t-5.79=15t | | 9h-(2h-4h+1)=38-2h |

Equations solver categories